Os editoriais do jornal O Paraná: análise sobre as relações discursivas e política partidária - Sales, Liliane Aparecida Marquardt (2015)
This work aims to reflect on the discursive relations evidenced in newspaper editorials "Parana" with partisan politics. The study corpus refers to the reading and analysis of fifteen editorials have stated regarding the hydroelectric plant Itaipu Binacional in the years 1979, 1984 and 2007. The entire study was based on the archaeological method advocated by Michel Foucault (2013) which allowed recognize the most varied emergency conditions and production of speech and respect beams contributing to the construction of favorable partisan discursive relations, or not, the federal government above us. To this end, it started with the assumption that the mass media constitute in oligopolies because defend their interests through the editorial, which propagates the discourse of these groups. As noted in this context the news can be seen as a product and market-driven. In the description of statements, it appears that the various linguistic marks corroborate the newspaper's intention to manifest their political position. In 1979, the newspaper company inclined to the interests proposed by the Federal Government that Itaipu would be national development reference, silencing the Discourse Formation in relation to the movement of struggle for land, which permeated society at that time. It is observed that in 1984, the country experiencing the transition from dictatorship to democracy, and "Paraná" explicit, in its editorial, the political clashes of this period and, through discourse, approaching opposition from FD to the regime current, showing the dispersion of speech. However, at times, editorials express regularity in his speech, directing it to the vainglorious FD uttered by the military. Already in 2007, in full democracy, the discourse presents a regularly when his editorials refer to Itaipu Binacional, as a synonym for development. By analyzing the statements, which address the issues on the plant, it can be seen that the regularity of the speech was given by bundles of relations in the political sphere that the news organization had in production periods of the studied editorials.